Effect of nitrogen and poultry manure on yield and nutrients uptake by maize (Zea mays) - YADAV, SUNITA; MEENA, RAMAWATAR; SEEMA, SEEMA; KUMAR, SANDEEP; SHARMA, D K (The Indian Journal of Agricultural Sciences, 2019)
From this study we can conclude that significantly increase the yield of maize due to integrated nitrogen management could be further attributed to increased growth and vigour of plant as evident from increased growth attributes. So, the treatment combinations (T10) of 125 kg/ ha Nitrogen through inorganics plus 10 t/ha poultry manure through organics were having significant difference as compared to all other. This might be due to ready supply of nutrients through inorganic in the initial stages of crop growth and slow release of nitrogen and steady supply of other nutrients over an extended period of crop growth by organics. Organics have a priming effect on the release of nitrogen from inorganic fertilizer. Moreover, thoroughly decomposed organics were used in these treatments which might have mobilized native nutrients from soils. Poultry manure showed higher yield and yield attributing characters due to faster mineralization of nitrogen with its narrow C:N ratio (15:1-20:1) as evident by its chemical composition. The proper dose of poultry manure can be used as a source of organic manure for sustainable maize production.